Formation and morphology of grain boundary proeutectoid pearlite in 100Mn13 steel during low temperature aging treatment. (December 2022) - Ding, Zhimin; Liang, Bo; Xu, Zhenfeng; Tian, Rujin; Dong, Linnan; Zhao, Jing
Abstract: The different morphologies of grain boundary proeutectoid pearlite formed in 100Mn13 steel, which was conducted by solution treatment at 1050 ℃ and followed by aging treatment respectively at 475 ℃ and 500 ℃, were studied by transmission electron microscope. The results show that the proeutectoid phase formed at austenite grain boundary is the pearlite composed of carbide and ferrite after low temperature aging treatment, rather than one phase of carbide or ferrite which currently is widely considered. And there are two kinds of growth mechanisms for the grain boundary proeutectoid pearlite as follows: (1) The grain boundary proeutectoid pearlite consists of one layer of carbides and one layer of ferrite jointly arranged continuously along grain boundary, the carbides are M3 C+M7 C3 mixed carbides, which is the leading phase of pearlite precipitation. (2) The grain boundary proeutectoid pearlite makes up short rod-like carbides and short rod-like ferrites arranged alternately along grain boundary, the carbide is M3 C carbide. Graphical Abstract: ga1